Anti‐TNF treatment during pregnancy and birth outcomes: A population‐based study from Denmark, Finland, and Sweden. Issue 3 (4th February 2020) - Bröms, Gabriella; Kieler, Helle; Ekbom, Anders; Gissler, Mika; Hellgren, Karin; Lahesmaa‐Korpinen, Anna‐Maria; Pedersen, Lars; Schmitt‐Egenolf, Marcus; Sørensen, Henrik T.; Granath, Fredrik
Abstract: Purpose: To study the risk of preterm birth, caesarean section, and small for gestational age after anti‐tumor necrosis factor agent treatment (anti‐TNF) in pregnancy. Methods: Population‐based study including women with inflammatory bowel disease, rheumatoid arthritis, ankylosing spondylitis, psoriatic arthritis, and psoriasis, and their infants born 2006 to 2013 from the national health registers in Denmark, Finland, and Sweden. Women treated with anti‐TNF were compared with women with nonbiologic systemic treatment. Adalimumab, etanercept, and infliximab were compared pairwise. Continuation of treatment in early pregnancy was compared with discontinuation. Odds ratios with 95% confidence intervals were calculated in logistic regression models adjusted for country and maternal characteristics. Results: Among 1 633 909 births, 1027 infants were to women treated with anti‐TNF and 9399 to women with nonbiologic systemic treatment. Compared with non‐biologic systemic treatment, women with anti‐TNF treatment had a higher risk of preterm birth, odds ratio 1.61 (1.29‐2.02) and caesarean section, 1.57 (1.35‐1.82). The odds ratio for small for gestational age was 1.36 (0.96‐1.92). In pairwise comparisons, infliximab was associated with a higher risk of severely small for gestational age for inflammatory joint and skin diseases but not for inflammatory bowel disease. Discontinuation of anti‐TNF had opposite effects on preterm birth for inflammatory bowel disease and inflammatory joint and skin diseases. Conclusions: Anti‐TNF agents were associated with increased risks of preterm birth, caesarean section, and small for gestational age. However, the diverse findings across disease groups may indicate an association related to the underlying disease activity, rather than to agent‐specific effects.